FIGURE 10 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 10. (A–B) Pectinida gen. et. sp. indet. (A) Cross section of an articulated specimen. (B) Internal mould of the upper valve. Note possible adductor muscle scar and a line close to the dorsal margin, representing a possible dorsal furrow. (C–G) Oxytoma octavia (d'Orbigny, 1850). (C) Lateral view of a small left valve internal mould with fragments of the shell preserved showing weak radial ornament. (D) Enlarged view of anterodorsal portion area showing weak byssal notch. (E) Lateral view of a large left valve showing well developed radial ornament composed of primary and secondary ribs. (F) Lateral view of a right valve; lack of ornament is caused by shell delamination. Note very weak posterior sulcus and flattening of the valve. Probable shape of auricle is shown with dashed line (evidence from other partial specimens). (G) Plasticine cast of right valve external mould. Note radial ornament composed of primary and secondary ribs. (H–K) Camptonectes (Costicamptonectes) aff. milnelandensis Fürsich, 1982. (H–I) Right valve internal mould with shell partially preserved showing some divaricating ornament preserved close to the posterior shell margin. (J–K) External mould of right valve of a specimen from the Dorsoplanites bed, showing radial ribs close to the anterior shell margin and divaricating ornament preserved close to the posterior shell margin. (L–O) Camptonectes (Camptochlamys) clathratus (Roemer, 1836). (L–M) Lateral view of poorly preserved left valve showing cancellate external ornament in ventral margin. (N–O) Lateral view of a disarticulated and compressed shell from the Dorsoplanites bed showing cancellate ornament. Note distinct anterior auricle in the right valve. (P–R) Pseudolimea arctica (Zakharov, 1966). (P) Lateral view of left valve internal mould with some shell preserved around the ventral margin, with V-shaped ribs on the outer shell surface and corresponding rounded ribs on the internal mould. (Q) Lateral view of right valve, with anterior and posterior auricles and lack of secondary ...